PERAN BUMDES GAJAH MADA DALAM MENANGANI FENOMENA BRAIN DRAIN DI DESA KEBONTUNGGUL, GONDANG, MOJOKERTO - Siti Wulandari; Yanuar Fauzuddin (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to determine the role of Gajah Mada Village Owned Enterprise in minimizing brain drain in Kebontunggul Village, Mojokerto Regency. This study used a qualitative approach with an explanatory case study type of research. Data collection techniques used are observation, interviews and documentation. Data analysis was carried out by analyzing relevant data according to the diagnostic elements, analyzing the responses of organizational actors, pattern matching, chain of evidence and cross check. The results of this study indicate that BUMDes Gajah Mada has implemented several strategies in order to minimize the brain drain phenomenon that occurred in Kebontunggul village, but the implementation of these strategies has not been effective in minimizing the brain drain phenomenon in Kebontunggul Village.